Repeated Galvanic Vestibular Stimulation Modified the Neuronal Potential in the Vestibular Nucleus. (27th May 2020) - Kim, Gyutae; Lee, Sangmin; Kim, Kyu-Sung
Abstract : Vestibular nucleus (VN) and cerebellar flocculus are known as the core candidates for the neuroplasticity of vestibular system. However, it has been still elusive how to induce the artificial neuroplasticity, especially caused by an electrical stimulation, and assess the neuronal information related with the plasticity. To understand the electrically induced neuroplasticity, the neuronal potentials in VN responding to the repeated electrical stimuli were examined. Galvanic vestibular stimulation (GVS) was applied to excite the neurons in VN, and their activities were measured by an extracellular neural recording technique. Thirty-eight neuronal responses (17 for the regular and 21 for irregular neurons) were recorded and examined the potentials before and after stimulation. Two-third of the population (63.2%, 24/38) modified the potentials under the GVS repetition before stimulation (p = 0.037 ), and more than half of the population (21/38, 55.3%) changed the potentials after stimulation (p = 0.209 ). On the other hand, the plasticity-related neuronal modulation was hardly observed in the temporal responses of the neurons. The modification of the active glutamate receptors was also investigated to see if the repeated stimulation changed the number of both types of glutamate receptors, and the results showed that AMPA and NMDA receptors decreased after the repeated stimuli by 28.32 and 16.09%, respectively, implying the modification in the neuronal amplitudes.